Queen of the hillbillies : writings of May Kennedy McCord - McCord, May K. (Chronicles of the Ozarks., 2022)
"Queen of the Hillbillies is a vibrant, long-overdue collection of the writings of May Kennedy McCord, who documented the traditions and history of her native Ozarks as one of the twentieth century's preeminent folklorists. This capacious volume features McCord's own multifaceted writing alongside correspondence, recollections, and poems from her readers and fellow writers"--